Corpus callosum demyelination associated with acquired stuttering. (21st April 2018) - Decker, Barbara McElwee; Guitar, Barry; Solomon, Andrew
Abstract : Compared with developmental stuttering, adult onset acquired stuttering is rare. However, several case reports describe acquired stuttering and an association with callosal pathology. Interestingly, these cases share a neuroanatomical localisation also demonstrated in developmental stuttering. We present a case of adult onset acquired stuttering associated with inflammatory demyelination within the corpus callosum. This patient's disfluency improved after the initiation of immunomodulatory therapy.